Study of the formation of alkaline electroless Ni-P coating on magnesium and AZ31B magnesium alloy (2017)
In this work, alkaline electroless Ni-P coatings were directly formed on commercial purity magnesium and AZ31B magnesium alloy substrates using a process that avoided the use of Cr(VI) compounds. The study focused on two aspects of coating formation: (i) the effect of the substrate roughness on the kinetics of the electroless Ni-P deposition process on magnesium; (ii) the morphological and chemical evolution of the coating on both magnesium and the AZ31B alloy. For these purposes, gravimetric measurements, scanning electron microscopy (SEM), X-ray diffraction (XRD), Rutherford backscattering spectrometry (RBS) and open-circuit potential (OCP) measurements were employed. It is shown that a relatively rough substrate promotes the rapid formation of the Ni-P coating on the substrate surface in comparison with smoother substrates. Furthermore, the presence of fluoride ions derived from the NH4HF2 reagent in the electroless Ni-P plating bath leads to formation of MgF2 a few seconds after immersion in the bath. Subsequently, crystals of NaMgF3, with a cubic morphology, are developed, which later become embedded in the Ni-P matrix. The presence of fluorine species passivates the substrate during coating formation and hence restricts the decomposition of the electroless Ni-P plating bath, which can occur due to release of Mg2 + ions. Finally, according to gravimetric measurements, SEM and XRD, the plating process is initially faster on magnesium than on the alloy. © 2017 Elsevier B.V.